Optimization of the Public Procurement System in The Context of Ensuring Economic Security - Israilov Baxodir (Scientific Trends, 2025)
This study examines the role of public procurement system optimization as a key factor in ensuring economic security. Public procurement accounts for a significant share of public expenditures and therefore represents a critical area of potential economic risk. The article analyzes major threats to economic security arising within procurement processes, including corruption, inefficient allocation of budgetary resources, and limited competition. Using a qualitative analytical approach based on international reports and best practices, the study identifies core optimization mechanisms such as digitalization, procedural standardization, and enhanced institutional control. The findings indicate that the implementation of integrated electronic procurement systems and risk‑oriented monitoring tools significantly contributes to transparency, fiscal stability, and sustainable economic development.
Keywords: Public procurement, economic security, optimization, digital governance, risk management.